Was the post-war international trade order bound to succeed while the Bretton Woods monetary order established in 1944 was doomed to fail? - de Urioste, Ricardo (2023)
This paper explores the reasons embedded in the original architecture of both the international trade and monetary regimes that determined different outcomes for both. It proposes that the original version of the Bretton Woods monetary regime showed faster its essential failures and basically had to be replaced as early as 1971, while the trade regime embodied in the GATT and later in the WTO managed to at least survive until present day. It posits that correspondence (or the lack of it) of the basic characteristics of the said regimes with the underlying political reality where the regimes would apply (in line with Ruggie´s depiction of «embedded liberalism») accounts for the differentiated outcomes. It explains that the international trade regime showed more flexible traits that allowed it to adjust to the underlying political and led to its survival. The lack of that adaptability element would likewise explain the early demise of the original Bretton woods scheme.